PENGARUH LABEL HALAL, KUALITAS PRODUK, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN KOPI KENANGAN - Isje Pradina (2021)
The halal industry in Indonesia is increasing every year, especially in the halal food sector Although the halal industry has increased, there are still many food commodities without a halal label. This study aims to determine the effect of halal label, product quality, service quality on purchasing decisions for Kopi Kenangan in Jabodetabek. This study uses a quantitative approach. The sample used in this study was 100 Kopi Kenangan consumers located in the Greater Jakarta area. Tools to get data is a questionnaire using a Likert scale. In this study using multiple linear regression analysis supported by Validity and Reliability test, Classical Assumption test, t-test and f-test using IBM SPSS Statistics software. The results obtained from this study are Halal Label (X1), Product Quality (X2), and Service Quality (X3) has a significant effect on purchasing decisions of Kopi Kenangan,, and all variables simultaneously have a significant influence on the purchasing decision of Kopi Kenangan.